Pengaruh Role Playing Berbantuan Media Audio Visual Terhadap Keterampilan Berbicara Siswa Sekolah Dasar Kelas IV - Ana Nur Saputri; Angga Setiawan; Wahyu Nugroho (Jurnal Riset Madrasah Ibtidaiyah, 2023)
This research was conducted to compare the application of role-playing models assisted by audio-visual media with conventional models assisted by media images on students' speaking skills. A sample of all grade IV students at SDN 1 Duren, totaling 15 people, was used as the experimental class and at SDN 1 Dermosari, totaling 12 people, was used as the control class. The research method is quantitative with the non-equivalent form of pretest and posttest control group design. The data collection was in the form of speaking skills test with reference to the speaking skills rubric. After analyzing the collected data, the researcher conducted a hypothesis test to find out a significant difference. Hypothesis test analysis data obtained 0.001 <0.05. The researcher concluded that there was a positive impact from the role-playing model assisted by audio-visual media on students' speaking skills which increased and enthusiasm for learning activities. It can be interpreted that the speaking skills of students at SDN 1 Duren are influenced by the role-playing model assisted by audio-visual media. It can be seen from the average results of the experimental class getting an average of 46.93 with a value of 68 as the highest score and 32 as the lowest score while the posttest experiment with an average of 85.86 with 96 as the highest score and 76 as the lowest score.